(untitled) (World Economics and Finance Bulletin, 2023)
The article expresses an opinion about the use of innovative processes in industrial enterprises and their importance, and the stages in the use of innovative processes by enterprises are analyzed. Also, the activities of enterprises and their use of innovative processes were analyzed. Also, according to the analysis, the innovation results of the enterprises were discussed